Assessing the quality of myopia prevention videos on Chinese short video platforms: a cross-sectional content analysis by source - Tao Li; Xiaodong Zhou; Kun Wang; Yulu Zhou; Meilin Li; Rong-Bin Liang; Rundong Yang (BMJ Open)
Objectives The prevalence of myopia has been rising, whereas prevention efforts have shown limited success. Educational short videos have become crucial sources for health information; however, their quality regarding myopia prevention is uncertain. This study aimed to evaluate the quality and content of short videos on myopia prevention disseminated via major Chinese short video platforms and compare content differences between healthcare professionals and non-professional creators.Design A cross-sectional content analysis.Setting Top-ranked videos from three dominant Chinese platforms (TikTok, Kwai and BiliBili) in 6–10 August 2024.Participants 284 eligible videos screened from 300 initial results using predefined exclusion criteria, including 97 videos from TikTok, 94 from BiliBili and 93 from Kwai.Methods Videos were assessed using the Global Quality Scale and a modified DISCERN tool. Content completeness was evaluated across six predefined domains. Videos were categorised by source (healthcare professionals vs non-healthcare professionals), and intergroup differences were statistically analysed.Results Of the 284 videos, 48.9% were uploaded by healthcare professionals and 51.1% by non-healthcare professionals. Overall video quality was suboptimal. Videos by ophthalmologists had significantly higher quality scores than those by other creators. Healthcare professionals focused more on definitions, symptoms and risk factors of myopia, whereas non-healthcare professionals emphasised prevention and treatment outcomes. Ophthalmologists more frequently recommended corrective lenses (including both standard spectacles and specially designed lenses for myopia control) and low-dose atropine, whereas non-healthcare professionals favoured vision training.Conclusions Significant quality gaps exist in myopia prevention videos. Healthcare professionals, particularly ophthalmologists, produce higher-quality and more comprehensive content. Strategic engagement by healthcare professionals in digital health communication and platform-level quality control is needed to improve public health literacy on myopia.